There are no in‐principle ethical objections to controlled voluntary SARS‐CoV‐2 infection. (4th January 2021) - Crummett, Dustin
Abstract: In response to the COVID‐19 pandemic, some authors have advocated a program of controlled voluntary infection (CVI) with SARS‐CoV‐2. Under CVI, during periods where the medical system is under capacity, volunteers from low‐risk groups would be intentionally infected after giving informed consent, and then quarantined until they have developed immunity. Proponents claim that this could have benefits for society, such as building herd immunity and ensuring that critical workers won't be incapacitated during the peak of the infection. They also claim that this could have benefits for individuals, such as being safely exempted from lockdown measures and (for individuals who are likely to be infected anyway) ensuring that the infection happens under relatively less dangerous conditions. Some respond that CVI would unethical. Here, I argue that, while CVI may or may not be ill‐advised for empirical reasons, there are no in‐principle ethical objections to it (i.e., if CVI would work as well as its proponents think, it would be ethical to implement it). I present three arguments for this conclusion. The first is an argument from informed consent: informed consent to relevantly similar medical procedures renders performing these procedures permissible, so informed consent to CVI would render it permissible. The second is an argument from reasonable beneficence: it draws on recent work by Caspar Hare on relevantly similar choices to argue that CVI is permissible. The third is an argument from precedent: smallpox variolation was permissible, and CVI is relevantly similar to that, so CVI is permissible.